HUBUNGAN PENGETAHUAN REMAJA PUTRI MENIKAH DINI TENTANG KEHAMILAN DENGAN KECEMASAN MENGHADAPI KEHAMILAN DI KECAMATAN PULOSARI KABUPATEN PEMALANG - ., Khomsatun; Trisnawati, yuli; Pantiawati, Ika (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
The first pregnancy for the women is one of the crisis periods in their life. The knowledge about the pregnancy is the important thing for the women that has been married, and also for the women who doing early marriage. With the knowledge about the appropriate knowledge for the women they will be more ready to face the pregnancy and they will not easy to get the anxiety.It is to find out the correlation of adolescence women knowledge who doing early marriage about the pregnancy and the anxiety to face the pregnancy in Sub district of Pulosari in Regency of Pemalang in 2010. This research is descriptive research that has the correlation with the cross sectional approach. Research population is all the adolescence women who doing early marriage (15-18 years old) and they who have not married that are 35 people. Technique of taking samples in this research is total sampling. Data analysis method in this research uses Rank Spearmen.The women adolescence women who doing early marriage about the pregnancy in Sub district Pulosari in Regency of Pemalang in 2011 most of them has the medium knowledge 18 women (51.4%). The anxiety in adolescence in facing the pregnancy in Sub district of Pulosari in Regency of Pemalang in 2011 which is most of them has little knowledge 20 people (57.1%). There is correlation between the women adolescence between the adolescence women knowledge who doing early marriage about the pregnancy and the anxiety to face the pregnancy in Sub district of Pulosary in Regency of Pemalang in 2011 (p=0.038). There is the correlation between the adolescence women knowledge who doing early marriage and the anxiety to face the pregnancy in Sub district of Pulosari in Regency of Pemalang in 2011. The adolescence women is supposed to more understand about the pregnancy so they can overcome the anxiety in facing the pregnancy.KEYWORDS : knowledge, anxiety, pregnancy, adolescent women, early marriage